Management of Root Resorption Using Chemical Agents: A Review - Mohammadi, Zahed; Cehreli, Zafer C; Shalavi, Sousan; Giardino, Luciano; Palazzi, Flavio; Asgary, Saeed (Iranian Endodontic Journal, 2016)
Root resorption (RR) is defined as the loss of dental hard tissues because of clastic activity inside or outside of tooth the root. In the permanent dentition, RR is a pathologic event; if untreated, it might result in the premature loss of the affected tooth. Several hypotheses have been suggested as the mechanisms of root resorption such as absence of the remnants of Hertwig's epithelial root sheath (HERS) and the absence of some intrinsic factors in cementum and predentin such as amelogenin or osteoprotegerin (OPG). It seems that a barrier is formed by the less-calcified intermediate cementum or the cementodentin junction that prevents external RR. There are several chemical strategies to manage root resorption. The purpose of this paper was to review several chemical agents to manage RR such as tetracycline, sodium hypochlorite, acids (citric acid, phosphoric acid, ascorbic acid and hydrochloric acid), acetazolamide, calcitonin, alendronate, fluoride, Ledermix and Emdogain. Keywords: Alendronate; Calcitonin; Citric Acid; Emdogain; Fluoride; Osteoclast; Root Resorption; Tetracycline